Differences in Pertussis Incidence by Income among Oregon Teens during an Outbreak. (3rd December 2015) - Robison, Steve G.; Liko, Juventila; Cieslak, Paul R.
Abstract : That disease and poverty are connected is a cornerstone of public health thought. In the case of pertussis, however, it is possible that the expected relationship to poverty is reversed. Grounds exist for considering that increases in income are associated with increases in pertussis rates, both in terms of real risk through social and network features and through the possibility of greater likelihood of care seeking and detection based on income. Using reported adolescent pertussis cases from a 2012 outbreak in Oregon, pertussis incidence rates were determined for areas grouped by zip code into higher, middle, and lower median household income. Adolescents of ages 13–16 years in higher income areas were 2.6 times (95% CI 1.8–3.8) more likely as all others to have reported pertussis during the 2012 outbreak and 3.1 (95% CI 1.4–6.5) times as likely as those in lower income areas. The higher pertussis rates associated with higher income areas were observed regardless of Tdap rate differences. These results suggest that income may be associated with disease risk, likelihood of diagnosis and reporting, or both. Further evaluation of this finding is warranted.